Permeability Evolution of an Intact Marble Core during Shearing under High Fluid Pressure - Yuan Wang; Yu Jiao; Shaobin Hu (Geofluids)
The progressive shear failure of a rock mass under hydromechanical coupling is a key aspect of the long-term stability of deeply buried, high fluid pressure diversion tunnels. In this study, we use experimental and numerical analysis to quantify the permeability variations that occur in an intact marble sample as it evolves from shear failure to shear slip under different confining pressures and fluid pressures. The experimental results reveal that at low effective normal stress, the fracture permeability is positively correlated with the shear displacement. The permeability is lower at higher effective normal stress and exhibits an episodic change with increasing shear displacement. After establishing a numerical model based on the point cloud data generated by the three-dimensional (3D) laser scanning of the fracture surfaces, we found that there are some contact areas that block the percolation channels under high effective stress conditions. This type of contact area plays a key role in determining the evolution of the fracture permeability in a given rock sample.